Applied Informatics and Cybernetics in Intelligent Systems Proceedings of the 9th Computer Science On-line Conference 2020, Volume 3 - Silhavy, Radek (Advances in Intelligent Systems and Computing, 2020)
XVI, 635 p. 252 illus., 122 illus. in color.